Development of Digital Marketing Management Through Websites and Social Media at Al-Furqon Vocational School (Educational Management, 2022)
This study aims to identify and produce digital marketing management products through websites and social media at Al-Furqon Vocational School. The type of research is Research and Development (R & D) using the Borg & Gall development model with modifications to the research and development steps by Sugiyono consisting of potential and problems, data collection, product design, design validation, design revision, product testing, product revisions, and final products. The research subjects are admins and teachers at SMK Al-Furqon. Data collection techniques are literature study, interviews, and questionnaires. The instruments used are expert validation questionnaires and product trials. The data analysis technique used is quantitative descriptive analysis. The results showed that digital marketing management through websites and social media was feasible to be tested after being declared valid by design experts and material experts. The results of the assessment of the research subject stated that it was very good and feasible to use. Based on the results of the study, it can be concluded that digital marketing management through websites and social media has met the categories of validity, practicality, and efficiency so that it is suitable for use in Al-Furqon Vocational School.